2020
DOI: 10.3390/pathogens9060496
|View full text |Cite
|
Sign up to set email alerts
|

S-methyl Methanethiosulfonate: Promising Late Blight Inhibitor or Broad Range Toxin?

Abstract: (1) Background: S-methyl methanethiosulfonate (MMTS), a sulfur containing volatile organic compound produced by plants and bacterial species, has recently been described to be an efficient anti-oomycete agent with promising perspectives for the control of the devastating potato late blight disease caused by Phytophthora infestans. However, earlier work raised questions regarding the putative toxicity of this compound. To assess the suitability of MMTS for late blight control in the field, the present study thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The final PCR products were analyzed by melting point analysis. The transcript levels of the oxidative stress marker (At3g46230; HSP17.4C1 ) 34 , and the salicylic acid-responsive genes AtPR-1 and AtPR-5 in Arabidopsis plants were calculated with At4g26410 ( expG ) as reference gene 60 and the comparative cycle threshold method (2 (-ΔΔCt) ) as mentioned above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final PCR products were analyzed by melting point analysis. The transcript levels of the oxidative stress marker (At3g46230; HSP17.4C1 ) 34 , and the salicylic acid-responsive genes AtPR-1 and AtPR-5 in Arabidopsis plants were calculated with At4g26410 ( expG ) as reference gene 60 and the comparative cycle threshold method (2 (-ΔΔCt) ) as mentioned above.…”
Section: Methodsmentioning
confidence: 99%
“…The expG gene was selected because Czechowski et al 60 specifically recommends expG as one of the top five reference genes to be used in biotic stress studies due to its high stability under such conditions. This high stability was confirmed in previous work of our laboratory 61 and others’ work 33 . In the present study, the stable expression of expG is reflected in the very small variation of the C q for expG .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that alcohol extracts (methanol and ethanol) and aqueous extract have the ability to inhibit the growth of all tested Candida species. These results are in agreement with Kalhoro, Farheen & Aqsa (2014) study, which found that the ethanol (Ovesná, Vachálková & Horváthová, 2004) S-Methyl methanethiosulphonate 0.07 --CH 3 SO 2 SCH 3 Ester, Antimutagenic agent and antimicrobial activity (Joller et al, 2020;Miguel et al, 2016) 1-Heptatriacotanol 0.23 --C 37 H 76 O Fatty alcohol…”
Section: Discussionsupporting
confidence: 89%
“…PeerJ reviewing PDF | (2020:07:51312:1:1:NEW 6 Nov 2020) Treatment of diarrhea and protozoa infections (Olajuyigbe et al, 2018). Heptanal 0.20 --C 7 H 14 O aldehyde antibacterial activity (Lamba, 2007 Ester, Antimutagenic agent and antimicrobial activity (Joller et al, 2020;Miguel et al, 2016 Anti-Viral and anti-tumour (Tolstikov et al, 2005 Manuscript to be reviewed (da Rocha et al, 2001). Dihydrosteviobiside --0.26 C32H52O13 No report was found.…”
Section: H-mentioning
confidence: 99%